2022
DOI: 10.1101/2022.02.09.479819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromosome-scale genome assembly of the diploid oat Avena longiglumis reveals the landscape of repetitive sequences, genes and chromosome evolution in grasses

Abstract: Background: Oat (Avena sativa, 2n=6x=42) is an important crop, and with its wild relatives including A. longiglumis (ALO, 2n=6x=14), has advantageous agronomic and nutritional traits. A de-novo chromosome-level ALO genome assembly was made to investigate diversity and structural genome variation between Avena species and other Poaceae in an evolutionary context, and develop genomic resources to identify the pangenome and economic traits within Pooideae. Results: The 3.85 gigabase ALO genome (seven pseudo-chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 160 publications
(324 reference statements)
0
10
0
Order By: Relevance
“…New long-molecule sequencing approaches are allowing assembly of Avena genome sequences, covering nearly 4,000Mbp in the diploids (Maughan et al, 2019; Liu et al 2022; Peng et al, 2022). High coverage shows the reciprocal translocations which are also revealed with the chromosomal probes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New long-molecule sequencing approaches are allowing assembly of Avena genome sequences, covering nearly 4,000Mbp in the diploids (Maughan et al, 2019; Liu et al 2022; Peng et al, 2022). High coverage shows the reciprocal translocations which are also revealed with the chromosomal probes.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome translocations are important for plant evolution (Martin et al, 2020; Wang et al, 2021; Biswas et al, 2022; Liu et al, 2022), and occur in diploids, and after hybrid or amphiploid formation; they lead to exchange of chromosome segments within and between the ancestral genomes. Comparative genetic analysis in the grass family, including major crops, showed that particular taxonomic units are characterized by different chromosome translocations in terms of their position on chromosomes, reciprocity, and number of breaks involved (Bardsley et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosome translocations are important for plant evolution ( Martin et al., 2020 ; Biswas et al., 2022 ; Liu et al., 2022 ; Wang et al., 2022 ), and occur in diploids, and after hybrid or amphiploid formation; they lead to exchange of chromosome segments within and between the ancestral genomes. Comparative genetic analysis in the grass family, including major crops, showed that particular taxonomic units are characterized by different chromosome translocations in terms of their position on chromosomes, reciprocity, and number of breaks involved ( Bardsley et al., 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis thaliana many Ty3- gypsy retroelements are present in pericentromeric heterochromatin region (Brandes et al, 1997b). Centromeric retroelements in maize (CRM) is a lineage of Ty3- gypsy retroelements (Jin et al, 2004), and the diploid oat Avena longiglumis (2 n =2 × =14; 3,850 Gb genome size) has specific LTR retrotransposons located at the centromeres (Liu et al, 2022), in all cases with other retroelement families dispersed along all chromosomes. Some of these repetitive elements may have a role in centromere functionality, although they may also accumulate in regions of the genome where there are few genes.…”
Section: Introductionmentioning
confidence: 99%